DEVELOPMENT OF APPLICATION-ASSISTED PERSUASION TEXT TEACHING MATERIALS FOR CLASS VII - Rantika Alycia Putri; Trisnawati Hutagalung (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This study aims to (1) describe the process of developing persuasive text teaching materials for class VIII students and (2) describe the feasibility of teaching persuasive texts for class VIII students. This type of research is research and development using the Borg and Gall model. as for the stages of research and development of persuasive text teaching materials through the stages of potential and problem analysis, data collection, product design, design validation, and revisions modified by Sugiyono to the fifth stage. The research sample was 30 class VIII students of SMP Negeri 2 Sibolangit using the Purposive Sample technique. Data collection techniques using observation, interviews, and questionnaires. The research instrument is material expert validation using Likert. Analysis of research data using descriptive qualitative study. The results of material expert validation obtained an overall percentage score of 83%, including the